Answer:
By solving the equation [tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] we found that [tex]x=\frac{23}{2} \text { or }=11 \frac{1}{2}[/tex]
Explanation:
Given equation,
[tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] to find x
Step: 1 Cross multiply the denominators 2(x-5)=6(x+6)
Step: 2 Open brackets and simplify the term 2x-10=6x+36
Step: 3 Bring x terms on one side and simplify the equation the equation obtained is following,
2x-6x=36+10
-4x=46
[tex]-x=\frac{46}{4}=\frac{23}{2}=11 \frac{1}{2}[/tex]
Therefore, we solved x value from the given equation [tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] as [tex]x=\frac{23}{2} \text { or }=11 \frac{1}{2}[/tex].